Trophoblastic Infiltration in Tubal Pregnancy Evaluated by Immunohistochemistry and Correlation with Variation of Beta-Human Chorionic Gonadotropin. (9th January 2014) - Ferreira, Danyelle Farias; Elito Júnior, Julio; Araujo Júnior, Edward; Stavale, João Norberto; Camano, Luiz; Moron, Antonio Fernandes
Abstract : Objective . To evaluate trophoblastic cell proliferation and angiogenesis in tubal pregnancy assessed by immunohistochemical study and their correlation with an average variation of β -hCG in an interval of 48 hours before surgery. Methods . A prospective study was conducted on 18 patients with a diagnosis of tubal pregnancy. The patients were divided into two groups of ectopic pregnancy of which 11 showed rise of β -hCG levels and 7 patients showed declining β -hCG levels in an interval of 48 hours prior to surgery. Trophoblastic cell proliferation and angiogenesis were assessed by Ki-67 and VEGF, respectively. Trophoblastic cell proliferation was assessed by Ki-67 and was classified into three groups (grade I: less than 1/3 of stained nuclei, grade II: 1/3 to 2/3 of the stained nuclei, and grade III: more than 2/3 of the nuclei stained). The cases analyzed for VEGF were divided into three groups (grade I: less than 1/3 of the stained cytoplasm; grade II: 1/3 to 2/3 of the stained cytoplasm; grade III: more than 2/3 of the stained cytoplasm). Statistical analysis was performed using the chi-square, ANOVA, and Kruskal-Wallis tests. Results . The mean variation in the serum β -hCG levels in 48 hours in tubal pregnancy patients correlated with trophoblastic cell proliferation assessed by Ki-67 and showed a decline of 13.46% in grade I, a rise of 45.99% in grade II, and ascension of 36.68% in grade III (P = 0.030 ). The average variation in the serum β -hCG in 48 hours, where angiogenesis was evaluated by VEGF, showed a decline of 18.35% in grade I, a rise of 32.95% in grade II, and ascension of 37.55% in grade III (P = 0.047 ). Conclusions . Our observations showed a direct correlation of increased levels of serum β -hCG in 48h period prior to surgery with higher trophoblastic cell proliferation assessed by Ki-67 and angiogenesis assessed by VEGF in tubal pregnancy.